Fracture, Fatigue, Failure and Damage Evolution, Volume 6 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Carroll, Jay.; Xia, Shuman; Beese, Allison M.; Berke, Ryan B.; Pataky, Garrett J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Fracture, Fatigue, Failure and Damage Evolution, Volume 6 of the Proceedings of the 2018 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the sixth volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Novel Experimental Methods Extreme Environments Interfacial Fracture Integration of Models & Experiments Mechanics of Energy & Energetic Materials Integration of Models & Experiments In Situ Techniques for Fatigue & Fracture Microscale & Microstructural Effects on Mechanical Behavior.
Chapter 1. Investigation of Deformation Mechanisms in Columnar Aluminum -- Chapter 2. Dynamic Shear Response of Soft Tissue Materials -- Chapter 3. Tensile Response of Ceramics at the Microscale -- Chapter 4. Development of Femtosecond Laser Based Microscale Fracture Methods -- Chapter 5. Programming Vanadium Dioxide based MEMS Mirror -- Chapter 6. Modelling & Simulation of Post Processed Foundry Fabricated Large, Out-of-Plane MEMS Energy Harvester -- Chapter 7. Measurement of the Visco-Elastic Properties of the Chinchilla Tympanic Membrane.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Building materials; Solid Mechanics; Characterization and Analytical Technique; Structural Materials